Modified poly (butylene terephthalate)-co-adipate and preparation method thereof

By adding a specific fourth monomer to PBAT and using a one-step polycondensation method, the problems of low glass transition temperature, poor heat resistance and insufficient fracture strength of PBAT materials are solved, and a higher Glass transition temperature and fracture strength simplify the preparation process and improve performance and hue.

CN119264397AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310831677.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The existing polybutylene terephthalate-co-adipate (PBAT) materials have low glass transition temperature, poor heat resistance and low fracture strength, resulting in defects and shortcomings in the processing process and subsequent applications.

Method used

Modified PBAT is prepared by adding a fourth monomer such as oxylic acid, furandicarboxylic acid, etc. to PBAT, and the molar ratio is adjusted, and esterification and polycondensation reaction are used to combine titanate and acetate as catalysts. The modified PBAT is prepared by one-step polycondensation method by combining titanate and acetate as catalysts. , improve its glass transition temperature and fracture strength.

Benefits of technology

The glass transition temperature and fracture strength of the modified PBAT are significantly improved, the heat resistance is improved, and the preparation process is simplified, avoiding the need for adding stabilizers and chain extenders, and achieving better product performance and hue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004327266300000161
    Figure BDA0004327266300000161
Patent Text Reader

Abstract

The invention relates to the technical field of biodegradable polyester, and provides modified poly (butylene terephthalate)-co-adipate and a preparation method thereof. The repetitive structure unit of the modified poly (terephthalic acid-co-butylene adipate) comprises a terephthalic acid structure unit, an adipic acid structure unit, a 1, 4-butylene glycol structure unit and a fourth monomer structure unit; the fourth monomer comprises at least one of oxalic acid, dimethyl oxalate, furandicarboxylic acid, dimethyl furandicarboxylate, malonic acid, dimethyl malonate, methylmalonic acid and diethyl methylmalonate. Compared with conventional pure PBAT, the modified poly (butylene terephthalate-co-butylene adipate) provided by the invention has higher glass transition temperature and breaking strength, lower melt index and better product hue, and can meet the use requirements of PBAT; and various problems caused by poor heat resistance and strength in the processing process and subsequent application of the conventional PBAT product are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable polyester, and more specifically to a modified polybutylene terephthalate-co-adipate and a preparation method thereof. Background Art

[0002] Polybutylene terephthalate-co-adipate (PBAT) is prepared from terephthalic acid (PTA), adipic acid (AA) and 1,4-butanediol (BDO) as raw materials through esterification and polycondensation. It is an aliphatic-aromatic copolyester with the biodegradability of aliphatic polyesters. It can be easily decomposed by various microorganisms in nature or enzymes in animals and plants, and finally produces carbon dioxide and water.

[0003] PBAT is a semi-crystalline polymer with a melting point of 120-130°C and a density of 1.17-1.30 g / cm 3 , the glass transition temperature is about -33°C, and the fracture strength is between 20 and 30MPa. The advantage of PBAT is that it is a thermoplastic biodegradable material, which can help solve the problem of white pollution and has good ductility, elongation at break, impact resistance, etc.; the disadvantage is that its glass transition temperature is low and its heat resistance is poor. At the same time, the melt index MFR (190°C, 2.16kg) of PBAT prepared by a one-step direct polycondensation method is above 10g / 10min. Although further chain extension or liquid phase viscosity enhancement of PBAT can make the MFR reach about 5g / 10min, it cannot increase its glass transition temperature, and the improvement of its fracture strength is also very limited, resulting in defects and deficiencies in the processing and subsequent applications.

[0004] At present, the method of blending modification is generally used to improve the performance of PBAT, that is, by adding a certain proportion of other polymers or inorganic substances to PBAT to improve the performance of PBAT blends. Some researchers have also tried to add other reactants during the PBAT polymerization reaction and synthesize modified PBAT by copolymerization to improve the defects of PBAT in certain properties. However, the existing PBAT modification methods have failed to effectively solve the shortcomings of PBAT, such as low glass transition temperature, poor heat resistance, and poor strength. In the processing and subsequent applications, PBAT products still have the defects of insufficient heat resistance and low strength.

[0005] Patent CN114561000A discloses a method for preparing polybutylene terephthalate-adipate modified by 1,4-cyclohexanedicarboxylic acid molecular structure, wherein 1,4-cyclohexanedicarboxylic acid and 1,4-butanediol are added to react to obtain a third esterification intermediate, and then the first and second esterification intermediates obtained by the esterification reaction of terephthalic acid and adipate are put into a polymerization reactor for polycondensation reaction. The tensile strength and elastic modulus of the modified PBAT polymer obtained are enhanced, but the intrinsic viscosity of the synthesized modified PBAT polymer is not high, which affects the actual mechanical properties, and there is no relevant experimental research information on the heat resistance.

[0006] Patent CN113861399A discloses a method for preparing a biodegradable polyester PBIAT. A certain proportion of isosorbide is added to terephthalic acid, adipic acid and 1,4-butanediol, and a catalyst is added to increase the temperature for polycondensation reaction to synthesize polyadipic acid-terephthalic acid-isosorbide-butylene glycol ester. The copolymer has good barrier properties and toughness, but the thermal properties and tensile strength of the copolymer are not disclosed. The description of the synthesis process is very general. Judging from the synthesis method adopted, the molecular weight of the obtained copolymer is low, and the low molecular weight of the polymer is obviously not conducive to improving its mechanical properties.

[0007] Patent CN113512187A discloses a transparent and degradable PBAT material, and its preparation method and use. During the preparation process of PBAT, isosorbide and isohexitol are added for prepolymerization, and a chain extender is added to synthesize a copolymer with a higher molecular weight. The transparency of the copolymer is improved, but the heat resistance and mechanical properties of the copolymer are not disclosed.

[0008] Patent CN110591057B discloses a method for synthesizing a biodegradable aliphatic-aromatic copolyester. During the esterification process of PTA and adipic acid, epoxy soybean oil is added to the PBAT molecular chain through an ester exchange reaction, and polycondensed at a higher temperature so that the molecular weight and intrinsic viscosity reach the target values. This method solves the problem of making it easier to achieve high target viscosity and molecular weight, reduce side reactions, and reduce the terminal carboxyl groups of the product. The heat resistance and mechanical properties of the copolymer are not disclosed. Summary of the invention

[0009] The object of the present invention is to provide a modified poly(butylene terephthalate-co-adipate) and a preparation method thereof, so as to solve the technical problem that the heat resistance and strength are not ideal in the prior art.

[0010] To achieve the above object, the technical solution adopted by the present invention is:

[0011] In the first aspect, the present invention provides a modified poly(butylene terephthalate-co-adipate), whose repeating structural units include terephthalic acid structural units, adipic acid structural units, 1,4-butanediol structural units and a fourth monomer structural unit; the fourth monomer includes at least one of oxalic acid, dimethyl oxalate, furandicarboxylic acid, dimethyl furandicarboxylate, malonic acid, dimethyl malonate, methylmalonic acid and diethyl methylmalonate.

[0012] According to some embodiments of the present invention, the molar ratio of the terephthalic acid structural unit, the adipic acid structural unit and the fourth monomer structural unit is 50:(30-45):(5-20), and the molar ratio of the sum of the moles of the terephthalic acid structural unit, the adipic acid structural unit and the fourth monomer structural unit to the 1,4-butanediol structural unit is 1:(1.2-2).

[0013] According to some embodiments of the present invention, the modified polybutylene terephthalate-co-adipate has a melt index MFR≤11.1 g / 10 min at 190° C. and 2.16 kg, a glass transition temperature Tg>10° C., a breaking strength of ≥27.5 MPa, and a hue b value of 3.0 to 9.6.

[0014] Generally, the glass transition temperature Tg of pure PBAT products is about -30°C, and the fracture strength is about 20MPa. The glass transition temperature Tg of the modified PBAT provided by the present invention is significantly higher than that of pure PBAT products, and the heat resistance is significantly improved. At the same time, the fracture strength is also improved to a certain extent, which solves the shortcomings of low glass transition temperature, poor heat resistance and low fracture strength of conventional pure PBAT products, and the product has better color.

[0015] According to some preferred embodiments of the present invention, the modified poly(butylene terephthalate-co-adipate) has a melt index MFR of 3.0 to 10.0 g / 10 min at 190° C. and 2.16 kg, a glass transition temperature Tg of 20.4 to 50.1° C., a breaking strength of 40.1 to 50.3 MPa, and a hue b value of 3.0 to 7.0.

[0016] In a second aspect, the present invention provides a method for preparing modified poly(butylene terephthalate-co-adipate), comprising: mixing terephthalic acid (PTA), adipic acid (AA), 1,4-butanediol (BDO) and a fourth monomer, and sequentially subjecting them to an esterification reaction and a polycondensation reaction to obtain the modified poly(butylene terephthalate-co-adipate);

[0017] The fourth monomer includes at least one of oxalic acid, dimethyl oxalate, furandicarboxylic acid, dimethyl furandicarboxylate, malonic acid, dimethyl malonate, methylmalonic acid, and diethyl methylmalonate.

[0018] In the existing pure PBAT preparation method, in addition to adding a catalyst, a stabilizer and other additives are also required during the esterification and polycondensation reaction process, and the performance of the PBAT product obtained by the direct one-step polycondensation method is often not ideal. However, the preparation method of the modified PBAT provided by the present invention does not require the addition of stabilizers, chain extenders, etc., and can directly prepare a modified PBAT product with a low melt index, high breaking strength, good heat resistance, and good hue through a one-step polycondensation method, which fully meets the use requirements.

[0019] According to some embodiments of the present invention, the molar ratio of the terephthalic acid, adipic acid and the fourth monomer is 50:(30-45):(5-20), and the molar ratio of the sum of the moles of the terephthalic acid, adipic acid and the fourth monomer to the 1,4-butanediol is 1:(1.2-2).

[0020] According to some embodiments of the present invention, the esterification catalyst added to the esterification reaction includes titanate and phosphate; preferably, the molar ratio of the titanate calculated by the amount of titanium contained to the phosphate calculated by the amount of phosphorus contained is (5-10):1, and / or the titanate includes at least one of tetrabutyl titanate and tetraisopropyl titanate, and / or the phosphate includes at least one of trimethyl phosphate, triethyl phosphate, and triphenyl phosphite.

[0021] According to some embodiments of the present invention, the condensation polymerization catalyst added to the condensation polymerization reaction includes titanate and acetate; preferably, the molar ratio of the titanate calculated based on the amount of titanium contained and the acetate calculated based on the amount of metal elements contained is (1 to 5): 1, and / or the titanate includes at least one of tetrabutyl titanate and tetraisopropyl titanate, and / or the acetate includes at least one of magnesium acetate, zinc acetate, aluminum acetate, and lithium acetate.

[0022] According to some embodiments of the present invention, the molar ratio of the esterification catalyst calculated by the amount of titanium contained to the molar sum of the terephthalic acid, adipic acid and the fourth monomer is 1:(1×10 3 ~10×10 3 ).

[0023] According to some embodiments of the present invention, the molar ratio of the polycondensation catalyst calculated by the amount of titanium contained to the molar sum of the terephthalic acid, adipic acid and the fourth monomer is 1:(1×10 3 ~10×10 3 ).

[0024] According to some embodiments of the present invention, the conditions of the esterification reaction include: a temperature of 170 to 240° C., a gauge pressure of 0 to 0.3 MPa, and a time of 3 to 5 hours.

[0025] According to some embodiments of the present invention, the conditions for the polycondensation reaction are: temperature of 240-260° C., absolute pressure of 40-400 Pa, and time of 1-5 hours.

[0026] According to some embodiments of the present invention, the preparation method further comprises: discharging, water cooling, casting and pelletizing after the polycondensation reaction is completed to obtain the modified polybutylene terephthalate-co-adipate.

[0027] In a third aspect, the present invention provides a modified poly(butylene terephthalate-co-adipate), which is prepared by the preparation method described in the second aspect.

[0028] In a fourth aspect, the present invention provides the use of the modified polybutylene terephthalate-co-adipate described in the first aspect or the third aspect in a biodegradable material.

[0029] The beneficial effects of the present invention are at least:

[0030] (1) The glass transition temperature Tg of the modified PBAT provided by the present invention is significantly higher than that of the pure PBAT product, and the heat resistance is significantly improved; at the same time, it has a lower melt index and higher fracture strength. The modified PBAT provided by the present invention can effectively solve the problems and shortcomings of the current pure PBAT products caused by poor heat resistance and strength during processing and subsequent applications.

[0031] (2) The modified PBAT provided by the present invention has a better product hue than pure PBAT.

[0032] (3) The preparation method of the modified PBAT provided by the present invention does not require the addition of a stabilizer or a chain extender, and the final modified PBAT product can be directly obtained by a one-step polycondensation method, which is simpler and more convenient than the currently used PBAT blending modification method.

[0033] (4) The modified PBAT provided by the present invention has good biodegradability and can eventually be completely degraded into harmless small molecules in nature, and can be widely used in the fields of lunch boxes, film bags, foam materials, disposable plastic products, etc. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0035] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0036] In each embodiment and comparative example of the present invention, each performance data is tested according to the following test method:

[0037] (1) Melt flow index (MFR): measured using a GT-7100 melt flow index meter produced by the High Speed ​​Rail Testing Instrument Company in accordance with GB / T3682.1-2018 at a temperature of 190°C and a weight of 2.16 kg.

[0038] (2) Glass transition temperature: measured using a DSC 131 differential thermal scanner (equipped with a refrigeration accessory) manufactured by Setaram. The specific method includes: weighing about 10 mg of sample and placing it into the DSC sample cell. Under the protection of N2, gradually heating the temperature from -50°C to 150°C at a rate of 10°C / min, and recording the heating curve.

[0039] (3) Hue b value: measured using a TC-PⅡG fully automatic colorimeter.

[0040] (4) Fracture strength: measured using a universal materials testing machine in accordance with the method and conditions specified in GB / T1040.1-2018.

[0041] Example 1

[0042] Esterification catalyst C1: tetrabutyl titanate (in terms of Ti molar amount) / trimethyl phosphate (in terms of P molar amount) = 5:1;

[0043] Polycondensation catalyst S1: tetrabutyl titanate (in terms of Ti molar amount) / magnesium acetate (in terms of Mg molar amount) = 1:1;

[0044] Preparation process:

[0045] S1. Weigh 332g (2mol) PTA, 263g (1.8mol) AA, 18g (0.2mol) oxalic acid (fourth monomer) and 432g (4.8mol) BDO into a reactor, add 4×10 -3 mol (in terms of titanium element) of esterification catalyst C1 to obtain a mixture;

[0046] Molar ratio: C1 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×103 ),

[0047] The fourth monomer / (PTA+AA+the fourth monomer)=5%;

[0048] S2. The mixture was stirred uniformly, and heated from room temperature to 170°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 170°C and a pressure of 0 (gauge pressure) for 5 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0049] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S1, stirred evenly, and carried out polycondensation reaction for 5 hours under the conditions of controlling the temperature to 240° C. and the pressure to 40 Pa (absolute pressure) to obtain a polycondensation product liquid;

[0050] Molar ratio: S1 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0051] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0052] Example 2

[0053] Esterification catalyst C2: tetraisopropyl titanate (in terms of Ti molar amount) / triethyl phosphate (in terms of P molar amount) = 10:1;

[0054] Polycondensation catalyst S2: tetraisopropyl titanate (in terms of Ti molar amount) / zinc acetate (in terms of Zn molar amount) = 5:1;

[0055] Preparation process:

[0056] S1. Weigh 332g (2mol) PTA, 234g (1.6mol) AA, 47g (0.4mol) dimethyl oxalate (fourth monomer) and 540g (6mol) BDO, put them into the reactor, add 4×10 -4 mol (in terms of titanium element) of esterification catalyst C2 to obtain a mixture;

[0057] Molar ratio: C2 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(10×10 3 ),

[0058] The fourth monomer / (PTA+AA+the fourth monomer)=10%;

[0059] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3 (gauge pressure) for 5 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0060] S3. Add 4×10 -4 mol (in terms of titanium element) of polycondensation catalyst S2, stirring evenly, controlling the temperature to 260° C. and the pressure to 400 Pa (absolute pressure) to carry out polycondensation reaction for 1 hour to obtain a polycondensation product liquid;

[0061] Molar ratio: S2 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(10×10 3 ).

[0062] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0063] Example 3

[0064] Esterification catalyst C3: tetraisopropyl titanate (in terms of Ti molar amount) / triphenyl phosphite (in terms of P molar amount) = 5:1;

[0065] Polycondensation catalyst S3: tetrabutyl titanate (in terms of Ti molar amount) / aluminum acetate (in terms of Al molar amount) = 2:1;

[0066] Preparation process:

[0067] S1. Weigh 332g (2mol) PTA, 175g (1.2mol) AA, 125g (0.8mol) furandicarboxylic acid (fourth monomer) and 720g (8mol) BDO into a reactor, add 4×10 -3 mol (in terms of titanium element) of esterification catalyst C3 to obtain a mixture;

[0068] Molar ratio: C3 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ),

[0069] The fourth monomer / (PTA+AA+the fourth monomer)=20%;

[0070] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3 (gauge pressure) for 3 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0071] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S3, stirring evenly, controlling the temperature to 260° C. and the pressure to 40 Pa (absolute pressure) to carry out polycondensation reaction for 5 hours to obtain a polycondensation product liquid;

[0072] Molar ratio: S3 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0073] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0074] Example 4

[0075] Esterification catalyst C4: tetrabutyl titanate (in terms of Ti molar amount) / triphenyl phosphite (in terms of P molar amount) = 8:1;

[0076] Polycondensation catalyst S4: tetraisopropyl titanate (in terms of Ti molar amount) / lithium acetate (in terms of Li molar amount) = 5:1;

[0077] Preparation process:

[0078] S1. Weigh 332 g (2 mol) PTA, 234 g (1.6 mol) AA, 74 g (0.4 mol) dimethyl furandicarboxylate (fourth monomer) and 540 g (6 mol) BDO, put them into the reactor, add 4 × 10 -3 mol (in terms of titanium element) of esterification catalyst C4 to obtain a mixture;

[0079] Molar ratio: C4 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ),

[0080] The fourth monomer / (PTA+AA+the fourth monomer)=10%;

[0081] S2. The mixture was stirred uniformly, and heated from room temperature to 170°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 170°C and a pressure of 0 (gauge pressure) for 5 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0082] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S4, stirring evenly, controlling the temperature to 250° C. and the pressure to 200 Pa (absolute pressure) to carry out polycondensation reaction for 4 hours to obtain a polycondensation product liquid;

[0083] Molar ratio: S4 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0084] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0085] Example 5

[0086] Esterification catalyst C5: tetraisopropyl titanate (in terms of Ti molar amount) / trimethyl phosphate (in terms of P molar amount) = 5:1;

[0087] Polycondensation catalyst S5: tetraisopropyl titanate (in terms of Ti molar amount) / zinc acetate (in terms of ZN molar amount) = 1:1;

[0088] Preparation process:

[0089] S1. Weigh 332g (2mol) PTA, 263g (1.8mol) AA, 21g (0.2mol) malonic acid (fourth monomer) and 432g (4.8mol) BDO into a reactor, add 4×10 -3 mol (in terms of titanium element) of esterification catalyst C5 to obtain a mixed material;

[0090] Molar ratio: C5 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ),

[0091] The fourth monomer / (PTA+AA+the fourth monomer)=5%;

[0092] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3 (gauge pressure) for 3 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0093] S3. Add 4×10 -4 mol (in terms of titanium element) of polycondensation catalyst S5, stirred evenly, and carried out polycondensation reaction for 4 hours under the conditions of controlling the temperature to 260° C. and the pressure to 40 Pa (absolute pressure) to obtain a polycondensation product liquid;

[0094] Molar ratio: S5 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(10×10 3 ).

[0095] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0096] Example 6

[0097] Esterification catalyst C6: tetraisopropyl titanate (in terms of Ti molar amount) / trimethyl phosphate (in terms of P molar amount) = 10:1;

[0098] Polycondensation catalyst S6: tetrabutyl titanate (in terms of Ti molar amount) / aluminum acetate (in terms of Al molar amount) = 5:1;

[0099] Preparation process:

[0100] S1. Weigh 332g (2mol) PTA, 263g (1.8mol) AA, 26g (0.2mol) dimethyl malonate (fourth monomer) and 540g (6mol) BDO into a reactor, add 4×10 -4 mol (in terms of titanium element) of esterification catalyst C6 to obtain a mixture;

[0101] Molar ratio: C6 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(10×10 3 ),

[0102] The fourth monomer / (PTA+AA+the fourth monomer)=5%;

[0103] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3MPa (gauge pressure) for 3 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0104] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S6, stirred evenly, and carried out polycondensation reaction for 5 hours under the conditions of controlling the temperature to 260° C. and the pressure to 100 Pa (absolute pressure) to obtain a polycondensation product liquid;

[0105] Molar ratio: S6 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0106] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0107] Example 7

[0108] Esterification catalyst C7: tetrabutyl titanate (in terms of Ti molar amount) / triethyl phosphate (in terms of P molar amount) = 5:1;

[0109] Polycondensation catalyst S7: tetraisopropyl titanate (in terms of Ti molar amount) / magnesium acetate (in terms of Mg molar amount) = 1:1;

[0110] Preparation process:

[0111] S1. Weigh 332g (2mol) PTA, 234g (1.6mol) AA, 47g (0.4mol) methylmalonic acid (fourth monomer) and 540g (6mol) BDO into a reactor, add 4×10 -3 mol (in terms of titanium element) of esterification catalyst C7 to obtain a mixture;

[0112] Molar ratio: C7 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ),

[0113] The fourth monomer / (PTA+AA+the fourth monomer)=10%;

[0114] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3MPa (gauge pressure) for 3 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0115] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S7, stirred evenly, and carried out polycondensation reaction for 4 hours under the conditions of controlling the temperature to 250° C. and the pressure to 40 Pa (absolute pressure) to obtain a polycondensation product liquid;

[0116] Molar ratio: S7 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0117] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0118] Example 8

[0119] Esterification catalyst C8: tetrabutyl titanate (in terms of Ti molar amount) / trimethyl phosphate (in terms of P molar amount) = 10:1;

[0120] Polycondensation catalyst S8: tetrabutyl titanate (in terms of Ti molar amount) / lithium acetate (in terms of Li molar amount) = 3:1;

[0121] Preparation process:

[0122] S1. Weigh 332 g (2 mol) of PTA, 234 g (1.6 mol) of AA, 70 g (0.4 mol) of diethyl methylmalonate (the fourth monomer) and 540 g (6 mol) of BDO, put them into a reactor, add 4 × 10 -3 mol (in terms of titanium element) of esterification catalyst C8 to obtain a mixture;

[0123] Molar ratio: C8 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ),

[0124] The fourth monomer / (PTA+AA+the fourth monomer)=10%;

[0125] S2. The mixture was stirred uniformly, and heated from room temperature to 240°C under the condition of a reaction pressure of 0 (gauge pressure); the mixture was controlled to be esterified at a temperature of 240°C and a pressure of 0.3MPa (gauge pressure) for 3 hours, and when the distillate reached more than 95% of the theoretical value, the esterification reaction was completed to obtain an esterified intermediate product;

[0126] S3. Add 4×10 -3 mol (in terms of titanium element) of polycondensation catalyst S8, stirred evenly, and carried out polycondensation reaction for 5 hours under the conditions of controlling the temperature to 260° C. and the pressure to 100 Pa (absolute pressure) to obtain a polycondensation product liquid;

[0127] Molar ratio: S8 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0128] S4. The liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain modified PBAT.

[0129] Example 9

[0130] The preparation process is similar to that of Example 1, except that the amounts of AA and oxalic acid (the fourth monomer) are changed to: the fourth monomer / (PTA+AA+the fourth monomer)=20%.

[0131] Example 10

[0132] The preparation process is similar to that of Example 2, except that the amount of polycondensation catalyst S2 added is 4×10 -3 mol (in terms of titanium element), S2 (in terms of titanium element) / (PTA+AA+fourth monomer)=1:(1×10 3 ).

[0133] Embodiment 11

[0134] The preparation process is similar to that of Example 1, except that the amounts of AA and oxalic acid (the fourth monomer) are changed to: the fourth monomer / (PTA+AA+the fourth monomer)=30%.

[0135] Example 12

[0136] The preparation process is similar to that of Example 1, except that the esterification catalyst C1 is replaced by an equal molar amount of tetrabutyl titanate (TBT) based on the titanium element.

[0137] Example 13

[0138] The preparation process is similar to that of Example 1, except that the esterification catalyst C1 is replaced by an esterification catalyst C9 in an equal molar amount based on the titanium element;

[0139] Esterification catalyst C9: tetrabutyl titanate (calculated by molar amount of Ti) / trimethyl phosphate (calculated by molar amount of P) = 3:1.

[0140] Embodiment 14

[0141] The preparation process is similar to that of Example 1, except that the esterification catalyst C1 is replaced by an esterification catalyst C in an equal molar amount based on titanium element. 10 ;

[0142] Esterification Catalyst C 10 : Tetrabutyl titanate (calculated by molar amount of Ti) / trimethyl phosphate (calculated by molar amount of P) = 15:1.

[0143] Embodiment 15

[0144] The preparation process is similar to that of Example 1, except that the polycondensation catalyst S1 is replaced by an equal molar amount of tetrabutyl titanate based on the titanium element.

[0145] Example 16

[0146] The preparation process is similar to that of Example 1, except that the polycondensation catalyst S1 is replaced by the polycondensation catalyst S9 in an equal molar amount based on the titanium element;

[0147] Polycondensation catalyst S9: tetrabutyl titanate (in terms of Ti molar amount) / magnesium acetate (in terms of Mg molar amount) = 1:2.

[0148] Embodiment 17

[0149] The preparation process is similar to that of Example 1, except that the polycondensation catalyst S1 is replaced by the polycondensation catalyst S in an equal molar amount based on the titanium element. 10 ;

[0150] Polycondensation catalyst S 10: Tetrabutyl titanate (in terms of Ti molar amount) / magnesium acetate (in terms of Mg molar amount) = 8:1.

[0151] Comparative Example 1

[0152] The preparation process is similar to that of Example 1, except that:

[0153] S1. Weigh 332g (2mol) PTA, 292g (2mol) AA and 432g (4.8mol) BDO into the reactor, add 4×10 -3 mol (in terms of titanium element) of esterification catalyst C1 to obtain a mixture;

[0154] Molar ratio: C1 (in terms of titanium element) / (PTA+AA)=1:(1×10 3 ).

[0155] Comparative Example 2

[0156] The preparation process is similar to that of Example 1, except that 18 g (0.2 mol) of oxalic acid is replaced by 34.4 g (0.2 mol) of 1,4-cyclohexanedicarboxylic acid.

[0157] Performance Evaluation

[0158] The PBAT products prepared in Examples 1-17 and Comparative Examples 1-2 were tested for melt index MFR (190° C., 2.16 kg), glass transition temperature Tg, hue b value, and breaking strength. The results are shown in the following table:

[0159]

[0160] It can be seen from the test results of Example 1 and Comparative Examples 1-2 that adding the fourth monomer in the process of preparing modified polybutylene terephthalate-co-adipate can reduce the melt index of the PBAT product, significantly improve its fracture strength and glass transition temperature, and also have a certain improvement effect on its hue b value.

[0161] It can be seen from the test results of Example 1, Example 9 and Example 11 that the higher the amount of the fourth monomer added, the better. When the molar ratio of the fourth monomer / (PTA+AA+fourth monomer) is between 5-20%, the increase in the amount of the fourth monomer added is conducive to further increasing the glass transition temperature of the PBAT product and further improving its heat resistance. When the molar ratio of the fourth monomer / (PTA+AA+fourth monomer) is increased to 30%, the molecular weight of the polymer product will be small due to the difficulty of polymerization, making the melt index of the PBAT product larger and its breaking strength significantly reduced.

[0162] It can be seen from the test results of Example 1 and Examples 12-14 that the esterification catalyst using a combination of titanate and phosphate can reduce the melt index of the PBAT product and improve its fracture strength compared with the use of titanate alone. In addition, the dosage ratio of titanate and phosphate in the esterification catalyst will also affect the performance of the prepared PBAT product. If the amount of phosphate is too small, it will not be able to reduce the melt index of the PBAT product and improve its fracture strength; if the amount of phosphate is too large, it will have an adverse effect on the melt index, fracture strength, glass transition temperature and product hue of the PBAT product.

[0163] It can be seen from the test results of Example 1 and Examples 15-17 that the use of a combination of titanate and acetate as a polycondensation catalyst can reduce the melt index of the PBAT product to a certain extent, improve its fracture strength, and significantly improve the hue of the PBAT product compared to the use of titanate alone. In addition, the dosage ratio of titanate and acetate in the polycondensation catalyst will also affect the performance of the prepared PBAT product. It is more appropriate that the molar ratio of titanate calculated by the amount of titanium contained and acetate calculated by the amount of metal elements contained is in the range of (1 to 5): 1. If the amount of acetate is too small, it cannot reduce the melt index of the PBAT product, improve its fracture strength, and improve the hue of the PBAT product; if the amount of acetate continues to increase, the performance of the PBAT product cannot be further improved.

[0164] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A modified polybutylene terephthalate-co-adipate, characterized in that: The repeating structural units of the modified poly(butylene terephthalate-co-adipate) include terephthalic acid structural units, adipic acid structural units, 1,4-butanediol structural units and fourth monomer structural units; the fourth monomer includes at least one of oxalic acid, dimethyl oxalate, furandicarboxylic acid, dimethyl furandicarboxylic acid, malonic acid, dimethyl malonate, methylmalonic acid and diethyl methylmalonate.

2. The modified polybutylene terephthalate-co-adipate according to claim 1, characterized in that: The molar ratio of the terephthalic acid structural unit, the adipic acid structural unit and the fourth monomer structural unit is 50:(30-45):(5-20), and the molar ratio of the sum of the moles of the terephthalic acid structural unit, the adipic acid structural unit and the fourth monomer structural unit to the 1,4-butanediol structural unit is 1:(1.2-2).

3. A method for preparing modified poly(butylene terephthalate-co-adipate), characterized in that: include: The modified poly(butylene terephthalate-co-adipate) is prepared by mixing terephthalic acid, adipic acid, 1,4-butanediol and a fourth monomer, and sequentially performing an esterification reaction and a polycondensation reaction; The fourth monomer includes at least one of oxalic acid, dimethyl oxalate, furandicarboxylic acid, dimethyl furandicarboxylate, malonic acid, dimethyl malonate, methylmalonic acid, and diethyl methylmalonate.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the terephthalic acid, adipic acid and the fourth monomer is 50:(30-45):(5-20), and the molar ratio of the sum of the moles of the terephthalic acid, adipic acid and the fourth monomer to the 1,4-butanediol is 1:(1.2-2).

5. The preparation method according to claim 3 or 4, characterized in that: The esterification catalyst added in the esterification reaction includes titanate and phosphate; preferably, the molar ratio of the titanate calculated by the amount of titanium contained to the phosphate calculated by the amount of phosphorus contained is (5-10):1, and / or the titanate includes at least one of tetrabutyl titanate and tetraisopropyl titanate, and / or the phosphate includes at least one of trimethyl phosphate, triethyl phosphate and triphenyl phosphite; And / or, the condensation polymerization catalyst added to the condensation polymerization reaction includes titanate and acetate; preferably, the molar ratio of the titanate calculated based on the amount of titanium contained and the acetate calculated based on the amount of metal elements contained is (1-5):1, and / or the titanate includes at least one of tetrabutyl titanate and tetraisopropyl titanate, and / or the acetate includes at least one of magnesium acetate, zinc acetate, aluminum acetate, and lithium acetate.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the esterification catalyst calculated by the amount of titanium contained to the molar sum of the terephthalic acid, adipic acid and the fourth monomer is 1:(1×10 3 ~10×10 3 ); and / or, the molar ratio of the polycondensation catalyst calculated by the amount of titanium contained to the molar sum of the terephthalic acid, adipic acid and the fourth monomer is 1:(1×10 3 ~10×10 3 ).

7. The preparation method according to any one of claims 3 to 6, characterized in that: The conditions of the esterification reaction include: temperature of 170-240° C., gauge pressure of 0-0.3 MPa, and time of 3-5 hours; And / or, the conditions of the polycondensation reaction are: temperature of 240-260° C., absolute pressure of 40-400 Pa, and time of 1-5 hours.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The preparation method further comprises: discharging, water cooling, casting and pelletizing after the polycondensation reaction is completed to obtain the modified polybutylene terephthalate-co-adipate.

9. A modified poly (butylene terephthalate-co-adipate) prepared by the preparation method described in any one of claims 3 to 8.

10. Use of the modified polybutylene terephthalate-co-adipate according to claim 1, claim 2 or claim 9 in biodegradable materials.

Citation Information

Patent Citations

  • A method for synthesizing biodegradable aliphatic-aromatic copolyesters

    CN110591057B

  • Biodegradable polyester PBIAT and preparation method thereof

    CN113861399A

  • Preparation method of polybutylene terephthalate / adipate butanediol copolyester

    CN101864068A

  • Biodegradable polyester and preparation method thereof

    CN103570925A

  • Preparation method of polybutylene adipate-terephthalate

    CN112266471A